Academic motivation and learner empowerment of Indonesian EFL students - Happy Cruzia Rini; Anita Triastuti (Journal of Education, Social & Communication Studies, 2024)
Learning is a process in which students experience change. During the learning process, teachers need to empower students to lead them to be independent in learning. Therefore, the present study focused on learner empowerment and academic motivation from the students' perspectives and the probable relationship. The participants were high school students who took English as a compulsory subject and were selected randomly. The researchers conducted mix method in this study. Two kinds of instruments were used as the quantitative data, namely the Academic Motivation Scale and the Learner Empowerment Scale. Meanwhile, open-ended questions were used as the instrument for the qualitative one. The result revealed that students' academic motivation and learner empowerment levels were at the moderate level. Moreover, the findings implied a statistically significant relationship between academic motivation and learner empowerment. Thus, higher motivation and empowerment in learning English are associated with each other. This expected study could explain the relationship between two crucial things in the classroom: motivation and empowerment.